Maternal and Adolescent Report of Mothers’ Weight-Related Concerns and Behaviors: Longitudinal Associations with Adolescent Body Dissatisfaction and Weight Control Practices - van den Berg, Patricia A. (Oxford University Press, 2010)
Objective This population-based study examined mothers’ weight-related concerns and behaviors (weight status, weight dissatisfaction, dieting, and encouraging child to diet) at baseline, as assessed by both mothers and adolescents, and associations with adolescents’ body dissatisfaction and weight control practices 5 years later. Methods Adolescents and their mothers (n = 443 pairs) were surveyed in 1998–1999; adolescents were resurveyed in 2003–2004. Results Baseline maternal report of higher levels of her weight-related concerns/behaviors was associated with greater body dissatisfaction in girls 5 years later, controlling for adolescent weight status and other covariates. Baseline maternal report of weight-related concerns/behaviors was also associated with greater prevalence of trying to lose weight in both boys and girls 5 years later. Baseline adolescent report of higher maternal weight-related concerns/behaviors was associated with a higher prevalence of trying to lose weight 5 years later in girls. Conclusions These findings highlight the importance of mothers’ weight-related concerns and behaviors for adolescents’ weight-related outcomes.